(3bUI GdHdOjjf ef Cgd aGSs - (3CHh GdbGSe Hf CMeO Hf Ydj GdRjGfis
(3ChdgG (B:s
(3hPdc Cfg deG GTJQi ehdGfG EOQjS QVi Gddg Yfg ehVY eOjfI aGS (B_ (3CefgG Gddg (B_(3hTQY ai HfGFgG aQZH GdfGS ai LhGQ Cgd GdHjJ s
(3BNQgG (B:s
(3hYdi JbOjQ Cfi CfGRY ajg de jLO ef jUZj dg a EfG ddg hEfG Edjg QGLYhf hUdi Gddg Ydi NjQ Ndbg SjOfG eMeO hBdg hMRHg CLejYf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B467 - (3U(B492s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B172s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B326 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(270 (3c(B) s
Keywords: (3GdJGQjNs